Pre-planning in crime scene management : search of criminology evidence - Jairam, Mahendran Sharma (Kulliyyah of Information and Technology, International Islamic University Malaysia, 2015)
This research elaborates major concerns of pre-planning in Crime Scene Management in search of criminology evidences gathered from specific crime scene investigation processes until the end of reconstruction of crime scene. The ultimate purpose of this analysis to identify imperfections in each preliminary level of administrating and managing the crime scene investigation while refers to Dr. Edmond Locard's Principle as a primary benchmark. Crime scene investigation is a subset of crime scene management. The basic steps of crime scene investigation are to emphasize and implement the procedures without fail. Hence, the measurement criteria on the pre-planning of crime scene management to be determined based on the process flow by specializations. One of the important elements is an approach or methodology to collect sources of information during the crime scene investigation but major is a capability of crime scene investigator to ensure those mentioned evidences and exhibits carefully handled. Successful of prosecution in any criminal hearings are rely heavily upon physical evidence discovered at crime scene and degree of effectiveness of crime scene management tremendously. Therefore, it is an essential for crime scene investigator to obtain certain criteria on proper crime scene management methods, techniques and applications. Suspect or an offender may escape from further accusations if crime scene management processes not applied in sequences and poor handling of crime scene investigation steps at time, perhaps will cause unnecessary confusion and conflict during the prosecution may resulted in suspect or an offender acquitted without further queries. As crime scene investigator must be sensitive towards overall scene processes and react professionally in coordinating of evidence management. The proper managing of crime scene investigation processes could link and support the investigator to determine the character of suspect through by testimonial evidences such as verbal statement taken from victim(s) or witnesses(s). Nevertheless, physical evidence as main targeted input in crime scene investigation usually found at the primary crime and secondary scene consists of many types such as human fingerprints, biological materials, paint chips, fibers, glass fragments, used weapons, accelerant and anything carefully or negligently utilized by the suspect at the crime scene. This dissertation paper literary aspire to provide the Crime Scene Investigator the important principles, notable steps and predominant in crime scene management and it effectiveness towards the end of the complying integrity investigation report.